2005
DOI: 10.1167/iovs.04-1020
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Multispectral Diffuse Reflectance Measurements of the Porcine Fundus

Abstract: Variations in fundus spectral reflectance with change in the illumination angle were found to deviate from Lambertian behavior, varying from Lambertian by 5% across the spectrum in one sample and 20% in a second sample. Intravitreal illumination resulted in markedly decreased extraneous reflections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…32 They are inexpensive, readily available, and provide a good model of the human eye. 33 They are also useful for preliminary testing before performing live swine or human eye studies with their requirements for a team of doctors, technicians, and associated costs.…”
Section: Testing the Rox-3 On An Enucleated Swine Eyementioning
confidence: 99%
“…32 They are inexpensive, readily available, and provide a good model of the human eye. 33 They are also useful for preliminary testing before performing live swine or human eye studies with their requirements for a team of doctors, technicians, and associated costs.…”
Section: Testing the Rox-3 On An Enucleated Swine Eyementioning
confidence: 99%
“…This inconsistency suggested that the combined effect of the cornea and fundus scattering only represent an equivalent model. Although the integral reflectance of the porcine fundus exhibited the Lambertian characteristic 37 and the Lambertian assumption has been adopted in previous studies, [38][39][40] the internal scattering from the multilayer fundus to the retina and directly absorbed at the fovea photoreceptors was not considered. Due to the lack of the experimental data on the angular distribution of internal fundus scattering, the Lambertian characteristic was used in the present model.…”
Section: Discussionmentioning
confidence: 99%
“…36 However, when the integral reflectance was considered, in vitro measurements of the porcine fundus 37 showed that the fundus behaved generally as a Lambertian reflector within 20% deviations. Also, previous studies had adopted the Lambertian assumption to either report the integral fundus reflectance 38,39 or to validate the fundus reflection model.…”
Section: Retina Fundusmentioning
confidence: 99%
“…The latter were probably not included in the evaluation, since nothing is written about them in these publications. To avoid this problem Sayler et al (2005) illuminated ex-vivo porcine eyes from the inside of the eye by inserting an illumination fiber in the vitreous of the eye [13] . With this set-up, an increase in reflectance of the inner eyewall with increasing wavelength was presented, too.…”
Section: Introductionmentioning
confidence: 99%